Fast dissolving moxifloxacin hydrochloride antibiotic drug from electrospun Eudragit L-100 nonwoven nanofibrous mats - Giram, Prabhanjan S.; Shitole, Ajinkya; Nande, Smita S.; Sharma, Neeti; Garnaik, Baijayantimala (Materials Science & Engineering C-Materials For Biological Applications, 2018)
Antimicrobial electrospun nonwoven Eudragit L-100 nanofibrous mats containing Moxifloxacin hydrochloride (MOX-HCL) were fabricated for fast dissolving drug delivery systems (DDSs) associated with wound infection. The morphological characterization of nanofibers using ESEM revealed that the average diameter of non-woven nanofibrous mats ranges 200-600 nm. The nanofiber showed cylindrical shape with crack on the surface. Differential scanning calorimetric (DSC) and Wide Angle X-ray diffraction (WAXRD) demonstrate that the drug exists in an amorphous state in the nanofibers. Nanofibrous mats were also tested for mechanical strength, contact angle, swelling assay, haemolysis and disintegration test. In vitro disintegration tests demonstrated that the dissolution of Eudragit L-100 fiber mats was within 25 s which was higher compared to the pure drug. The Eudragit nanofibers showed pH-dependent drug release profiles, with slow release at pH 1.2 and burst release (around 30 s) at pH 6.8. The in-vitro quantitative and qualitative antimicrobial assay showed that the developed Eudragit L-100 nanofibrous mats with MOX-HCL concentration of 1%, 5% and 15 wt% exhibited antibacterial activities against both gram positive (Staphylococcus aureus) and gram negative (Escherichia coli) bacteria. The invitro cytotoxicity assay using mouse fibroblast NIH/3T3 cells demonstrated significant biocompatibility of nanofiber mats. As per the results of biological evaluation, Eudragit L-100 nanofibrous mats with 1wt% MOX-HCL could be a suitable substrate for biomedical applications. Eudragit L-100 nanofibrous mats containing Moxifloxacin hydrochloride (MOX-HCL) showed immediate DDSs for localized drug release in the wound infection at slightly acidic or alkaline conditions where faster drug release rate is required for wound healing.

Clopidogrel eluting electrospun polyurethane/polyethylene glycol thromboresistant, hemocompatible nanofibrous scaffolds - Shitole, Ajinkya A.; Giram, Prabhanjan S.; Raut, Piyush W.; Rade, Priyanka P.; Khandwekar, Anand P.; Sharma, Neeti; Garnaik, Baijayantimala (Journal of Biomaterials Applications, 2019)
Biomaterials used as blood-contacting material must be hemocompatible and exhibit lower thrombotic potential while maintaining hemostasis and angiogenesis. With the aim of developing thromboresistant, hemocompatible nanofibrous scaffolds, polyurethane/polyethylene glycol scaffolds incorporated with 1, 5, and 10 wt% Clopidogrel were fabricated and evaluated for their physiochemical properties, biocompatibility, hemocompatibility, and antithrombotic potential. The results of physicochemical characterization revealed the fabrication of nanometer-sized scaffolds with smooth surfaces. The incorporation of both polyethylene glycol and Clopidogrel to polyurethane enhanced the hydrophilicity and water uptake potential of polyurethane/polyethylene glycol/Clopidogrel scaffolds. The dynamic mechanical analysis revealed the enhancement in mechanical strength of the polyurethane/polyethylene glycol scaffolds on incorporation of Clopidogrel. The polyurethane/polyethylene glycol/Clopidogrel scaffolds showed a tri-phasic drug release pattern. The results of hemocompatibility assessment demonstrated the excellent blood compatibility of the polyurethane/polyethylene glycol/Clopidogrel scaffolds, with the developed scaffolds exhibiting lower hemolysis, increased albumin and plasma protein adsorption while reduction in fibrinogen adsorption. Further, the platelet adhesion was highly suppressed and significant increase in coagulation period was observed for Clopidogrel incorporated scaffolds. The results of cell adhesion and cell viability substantiate the biocompatibility of the developed nanofibrous scaffolds with the HUVEC cell viability on polyurethane/polyethylene glycol, polyurethane/polyethylene glycol/Clopidogrel-1, 5, and 10% at day 7 found to be 12.35, 13.36, 14.85, and 4.18% higher as compared to polyurethane scaffolds, and the NIH/3T3 cell viability found to be 35.27, 70.82, 36.60, and 7.95% higher as compared to polyurethane scaffolds, respectively. Altogether the results of the study advocate the incorporation of Clopidogrel to the polyurethane/polyethylene glycol blend in order to fabricate scaffolds with appropriate antithrombotic property, hemocompatibility, and cell proliferation capacity and thus, might be successfully used as antithrombotic material for biomedical application.
Keywords: adhesion; cardiovascular; coagulation; electrospinning; Hemocompatible; platelet

Evaluation of biocompatibility of synthesized low molecular weight PLGA copolymers using zinc L-proline through green route for biomedical application - Giram, Prabhanjan S.; Garnaik, Baijayantimala (Polymers for Advanced Technologies, 2021)
Poly(lactide-co-glycolide) (PLGA) copolymers were synthesized by ring opening polymerization in presence of zinc proline and stannous octoate in bulk through green route and were designated as PLGA-1 and PLGA-2 respectively. These copolymers were characterized using NMR, SEC, DSC, X-ray and MALDI-TOF analysis. For the first time, the low molecular weight of PLGA (similar to 11,000 Da) was mainly targeted to explore acute oral toxicity in the presence of zinc L-proline and stannous octoate. The haemolysis and cell viability assay were carried out for in-vitro cytotoxicity assessment. Haemolysis assay of PLGA-2 was confirmed and haemolytic potential exceeded limit of American society of testing of material standard. The cell viability study using fibroblast cell lines (NIH3T3), exhibited statistically significant difference in results between PLGA-1 and PLGA-2. The acute toxicity study was performed in Balb/c mice for biomarker, hematological and histopathological analysis. No mortality was observed during the entire observation period, and no macroscopic change of the organs was observed in PLGA-1 treated group where PLGA-2 treated group showed sign of toxicity. The results obtained from in-vitro and in-vivo studies suggested that PLGA-2 was toxic whereas PLGA-1 was nontoxic in nature. Therefore, PLGA-1 can be regarded as biocompatible biomaterials for potential for drug delivery and biomedical application.
Keywords: OECD-420; poly (lactide-co-glycolide); ring opening polymerization; Stannous octoate; zinc L-Proline

Green synthesis of methoxy-poly(ethylene glycol)-block-poly(l-lactide-co-glycolide) copolymer using zinc proline as a biocompatible initiator for irinotecan delivery to colon cancer in vivo - Giram, Prabhanjan S.; Wang, Julie Tzu-Wen; Walters, Adam A.; Rade, Priyanka P.; Akhtar, Muhammad; Han, Shunping; Faruqu, Farid N.; Abdel-Bar, Hend M.; Garnaik, Baijayantimala; Al-Jamal, Khuloud T. (Biomaterials Science, 2021)
Poly(lactic-co-glycolic acid) (PLGA) is the most commonly described biocompatible copolymer used in biomedical applications. In this work, a green synthetic approach based on the biocompatible zinc proline complex, as an initiator for PLGA synthesis, is reported for the first time for the synthesis of methoxy-poly(ethylene glycol)-block-poly(l-lactic-co-glycolic acid) (mPEG-PLGA). mPEG-PLGA with controlled molecular weight and narrow polydispersity was synthesised. Its potential for delivery of irinotecan (Ir), a poorly water-soluble chemotherapeutic drug used for the treatment of colon and pancreatic cancer, was studied. Nanoparticles of controlled size (140-160 nm), surface charge (similar to-10 mV), release properties and cytotoxicity against CT-26 (colon) and BxPC-3 (pancreatic) cancer cells, were prepared. Tumor accumulation was confirmed by optical imaging of fluorescently labelled nanoparticles. Unlike Tween (R) 80 coated NP-Ir, the Pluronic (R) F-127 coated NP-Ir exhibits significant tumor growth delay compared to untreated and blank formulation treated groups in the CT-26 subcutaneous tumor model, after 4 treatments of 30 mg irinotecan per kg dose. Overall, this proof-of-concept study demonstrates that the newly synthesized copolymer, via a green route, is proven to be nontoxic, requires fewer purification steps and has potential applications in drug delivery.

Physicochemical and in vitro antibacterial evaluation of metronidazole loaded eudragit S-100 nanofibrous mats for the intestinal drug delivery - Rade, Priyanka P.; Giram, Prabhanjan S.; Shitole, Ajinkya A.; Sharma, Neeti; Garnaik, Baijayantimala (Advanced Fiber Materials, 2021)
Metronidazole (MTZ) loaded Eudragit S-100 (ES-100) nonwoven nanofibrous mats were successfully electrospun and evaluated for intestinal drug delivery. MTZ was varied in the range of 1–15% (w/w) in ES-100 nanofibrous mats, the morphological characterization of nanofibrous mats was carried out using FE-SEM and the average diameter of nanofiber was found in the range 150–600 nm. WAXD and DSC demonstrated the amorphous nature of MTZ in ES-100 nanofibrous mats. Their contact angle analysis confirmed the hydrophobic nature. The mechanical strength of ES-100 nanofibrous mats decreased with increasing MTZ concentration. The drug release profiles showed 74% MTZ release from ES-100d within 2 h at pH 6.8 which is the colonic environment. Antibacterial activities against gram-positive bacteria (Staphylococcus aureus) and gram-negative bacteria (Escherichia coli) showed that the ES-100 nanofibrous mats loaded with MTZ exhibited good activity.

Engineered PLGA core-lipid shell hybrid nanocarriers improve the efficacy and safety of irinotecan to combat colon cancer - Giram, Prabhanjan S.; Nimma, Ramakrishna; Bulbule, Anuradha; Yadav, Amit Singh; Gorain, Mahadeo; Radharani, Nalukurthi Naga Venkata; Kundu, Gopal C.; Garnaik, Baijayantimala (ACS BIOMATERIALS SCIENCE & ENGINEERING, 2024)
Keywords: BULK-POLYMERIZATION; Drug-delivery; LIPOSOMAL DOXORUBICIN

Poly(d,l-lactide-co-glycolide) surface-anchored biotin-loaded irinotecan nanoparticles for active targeting of colon cancer - Giram, Prabhanjan S.; Nimma, Ramakrishna; Bulbule, Anuradha; Yadav, Amit Singh; Gorain, Mahadeo; Radharani, Nalukurthi Naga Venkata; Kundu, Gopal C.; Garnaik, Baijayantimala (ACS Omega, 2024)
A poly-(d,l-lactide-co-glycolide) (PLGA) copolymer was synthesized using the ring-opening polymerization of d,l-lactide and glycolide monomers in the presence of zinc proline complex in bulk through the green route and was well characterized using attenuated total reflectance-Fourier transform infrared, H-1 and C-13 nuclear magnetic resonance, gel permeation chromatography, differential scanning calorimetry, X-ray diffraction, matrix-assisted laser desorption/ionization time-of-flight, etc. Furthermore, PLGA-conjugated biotin (PLGA-B) was synthesized using the synthesized PLGA and was employed to fabricate nanoparticles for irinotecan (Ir) delivery. These nanoparticles (PLGA-NP-Ir and PLGA-B-NP-Ir) were tested for physicochemical and biological characteristics. PLGA-B-NP-Ir exhibited a stronger cellular uptake and anticancer activity as compared to PLGA-NP-Ir in CT-26 cancer cells (log p < 0.05). The accumulation and retention of fluorescence-labeled nanoparticles were observed to be better in CT-26-inoculated solid tumors in Balb/c mice. The PLGA-B-NP-Ir-treated group inhibited tumor growth significantly more (log p < 0.001) than the untreated control, PLGA-NP-Ir, and Ir-treated groups. Furthermore, no body weight loss, hematological, and blood biochemical tests demonstrated the nanocarriers' nontoxic nature. This work presents the use of safe PLGA and the demonstration of a proof-of-concept of biotin surface attached PLGA nanoparticle-mediated active targeted Ir administration to combat colon cancer. To treat colon cancer, PLGA-B-NP-Ir performed better due to specific active tumor targeting and greater cellular uptake due to biotin.